PERBEDAAN KENAIKAN BERAT BADAN AKSEPTOR KB SUNTIK 1 BULAN DENGAN AKSEPTOR KB SUNTIK 3 BULAN DI TPMB DIAN RENATA DESA JOHO KECAMATAN PASIRIAN KABUPATEN LUMAJANG - ENI ANGGRAENI; NOVA HIKMAWATI; FARIANINGSIH FARIANINGSIH (NHM PRESS, 2023)
One month and three months injection contraceptive both contain the hormone progesterone which has an effect on increasing appetite, the content of the hormone progesterone in DMPA 150 mg injection KB and 25 mg combination injection KB. 1 month with a 3-month injectable kb acceptor at TPMB Dian Renata. The research method uses a comparison with a cross-sectional approach. The research sample was 1- month injection family planning acceptors and 3- month injection family planning acceptors, totaling 60 people. Data collection instruments are in the form of questionnaires and observation sheets. Data were analyzed by Mann Whitney test. The results showed that 1-month injection family planning acceptors at TPMB Dian Renata mostly did not experience weight gain as many as 23 people (76.7%). The 3-month injection KB acceptors at TPMB Dian Renata mostly experienced an increase in body weight of 21 people (70%), there was a difference in weight gain between 1-month injection KB acceptors and 3-month injection KB acceptors at TPMB Dian Renata (p=0.001). The conclusion of this study is that there is a difference in the weight gain of 1- month injection family planning acceptors and 3-month injection family planning acceptors at TPMB Dian Renata, Joho village, Pasirian, Lumajang. Suggestions from this study can be used as a reference for educational institutions, health services, and researchers to reduce the risk of side effects of family planning, especially in weight gain in family planning acceptors.